CHARACTERISTICS OF GAS HYDRATE OCCURRENCES ASSOCIATED WITH MUD DIAPIRISM AND GAS ESCAPE STRUCTURES IN THE NORTHWESTERN SEA OF OKHOTSK - Lüdmann T.; Wong H.K. (My University, 2003)
An interpretation of 8450 line-km of seismic reflection data acquired during four cruises in the northwestern Sea of Okhotsk shows widespread occurrence of free gas or gas hydrates in the sediment. This occurrence is documented seismically by gas escape structures, acoustic blanking, and by a bottom simulating reflector (BSR). Gas escape structures and vents are concentrated on the northern Sakhalin continental margin. Here, they are associated with local tectonic movements along a N–S trending dextral shear system (the Inessa Shear Zone). Mud diapirism is common in the Derugin Basin where compression dominates. This diapirism is probably closely related to the gas accumulations in the sediment below the base of the gas hydrate stability zone (BGHSZ). Conductive heat flow derived from the BSR depth distribution averages about 30±8 mW m−2. Only adjacent to basement highs and around the Inessa Shear Zone do values higher than 80±22 mW m−2 occur. These high values are attributed to an elevated geothermal gradient in the tectonically active zone where fluid venting takes place. Areas of drift sedimentation and mass wasting, where sedimentation rates are high, are characterised by computed heat flow values below 30±8 mW m−2. However, these values must be corrected upwards by 3–20% depending on the sedimentation rate applicable (3.8–100 cm/kyr). The total amount of methane preserved in the hydrate stability zone (HSZ) and trapped as free gas beneath the BSR is estimated at 17±14×1012 m3 for the northwestern Sea of Okhotsk and 15±12×1013 m3 for the entire Sea of Okhotsk. The latter figure represents about 0.8% of the global reservoir of methane gas from hydrates. Our study documents that the semi-enclosed Sea of Okhotsk offers favourable conditions for the accumulation of gas in its sediments on account of its subarctic climate and the prevailing hydrologic regime. These conditions include high primary productivity, low bottom water temperatures and high sedimentation rates.
Keywords: gas hydrate; methane; heat flow; mud diapirism; BSR; Sea of Okhotsk